Overlapping Phenotypes in Osteopetrosis and Pycnodysostosis in Asian-Indians - Parminder Kaur (Hindawi Limited, 2021)
Osteopetrosis is a disorder characterized by high bone density, hepatosplenomegaly, visual and hearing loss, and anemia. Pycnodysostosis presents with short stature, acroosteolysis, and dense bones. We, hereby, present here a family with autosomal dominant osteopetrosis and also children with recessive osteopetrosis and pycnodysostosis. The molecular confirmation was done in 3 cases. Genetic heterogeneity in clinical presentation is discussed here. Further studies will help in identifying epigenetic alterations and population-specific variants and also developing targeted therapies.